h - Han, Duck-Jong.; Kenmochi, Takashi; Shyr, Yi-Ming.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book is the first to provide a thorough overview of the experience of pancreas transplantation in Asian countries, including in particular Korea, Taiwan, and Japan. Recent trends are identified and attention drawn to differences in comparison with the United States and Europe. Such differences relate, for example, to the history of pancreas transplantation, the operative procedure, and the organ-sharing system. In addition, the insulin-secreting ability of pancreatic islet cells is thought to vary depending on race. Beyond these aspects, the coverage also encompasses ABO-incompatible living donor pancreas transplantation, which is very rarely performed elsewhere in the world. By introducing the number, technique, and outcomes of pancreas transplantation in Asian countries, the book will hopefully further stimulate the pancreas transplantation program in this region and beyond. It will be of value for all medical professionals in the field and will be informative for diabetic patients receiving insulin treatment in Asia.
1. Introduction -- 2. History of pancreas transplantation.-a. General/Japan/Korea/Taiwan -- 3. Indication of pancreas transplantation(Donor and Recipient) -- a. General/Japan/Korea/Taiwan -- 4. Pre operative evaluation -- a. General/Japan/Korea/Taiwan -- 5. Surgical aspect of pancreas transplantation -- a. General/Japan/Korea/Taiwan -- 6. Post operative management(general care,immunosuppressant, graft monitoring etc) -- a. General/Japan/Korea/Taiwan -- 7. Outcomes -- a. General/Japan/Korea/Taiwan -- 8. Complication -- a. General/Japan/Korea/Taiwan -- 9. Conclusion.
Keywords: Transplantation of organs, tissues, etc; Transplantation; Pancreas Transplantation -- methods; Pancreas Transplantation -- adverse effects; Pancreas Transplantation -- trends; Tissue Donors; Treatment Outcome; Blood Group Incompatibility -- complications; Asia